Die Fariseërs - Botha, Pieter J. J. (HTS teologiese studies, 2003)
The Pharisees The article shows that conventional depictions of the historical Pharisees are problematic. The difficulties of portraying the “other” are briefly noted, but in the main, this discussion deals with the proper use of the sources for the purpose of studying the historical Pharisees. After all, the question “what do we know about the Pharisees” presupposes an answer to “how do we know what we know”. As with so many other aspects of first-century Judaism, questions, rather than answers abound.